System design and calibration of SITARA - A global 21 cm short spacing interferometer prototype - Thekkeppattu, Jishnu; McKinley, Ben; Trott, Cathryn; Jones, Jake; Ung, Daniel (CAMBRIDGE UNIV PRESS, 2022)
Global 21-cm experiments require exquisitely precise calibration of the measurement systems in order to separate the weak 21-cm signal from Galactic and extragalactic foregrounds as well as instrumental systematics. Hitherto, experiments aiming to make this measurement have concentrated on measuring this signal using the single element approach. However, an alternative approach based on interferometers with short baselines is expected to alleviate some of the difficulties associated with a single element approach such as precision modelling of the receiver noise spectrum. Short spacing Interferometer Telescope probing cosmic dAwn and epoch of ReionisAtion (SITARA) is a short spacing interferometer deployed at the Murchison Radio-astronomy Observatory (MRO). It is intended to be a prototype or a test-bed to gain a better understanding of interferometry at short baselines, and develop tools to perform observations and data calibration. In this paper, we provide a description of the SITARA system and its deployment at the MRO, and discuss strategies developed to calibrate SITARA. We touch upon certain systematics seen in SITARA data and their modelling. We find that SITARA has sensitivity to all sky signals as well as non-negligible noise coupling between the antennas. It is seen that the coupled receiver noise has a spectral shape that broadly matches the theoretical calculations reported in prior works. We also find that when appropriately modified antenna radiation patterns taking into account the effects of mutual coupling are used, the measured data are well modelled by the standard visibility equation.